Federalism and Historical Voting on the U.S. Supreme Court. (3rd July 2018) - Parker, Christopher M.
ABSTRACT: A large body of scholarship has sought to explain the influences on the Supreme Court's decision-making. However, much of this research focuses on the modern era. Given the Court's institutional weaknesses in early American history, there is good reason to believe that early Supreme Court justices behaved differently than their contemporary counterparts. This article develops a dataset of federalism cases from 1789 to 2007 in order to analyze the role of ideology in the Court's federalism decisions throughout different eras of American history. This area of law is particularly useful for comparison given the early and enduring saliency of the boundaries between state and federal authority. The data reveal evidence that ideological voting developed over time as the Court paid more attention to legal and political factors as it developed its institutional legitimacy throughout the 1800s.